Etiology and Pathogenesis of Cholangiocarcinoma : Introduction to the Association with Liver Fluke Infection - Sripa, Banchob; Yongvanit, Puangrat; Pairojkul, Chawalit (Srinagarind Medical Journal, 2013)
Full text in PDF file